1993
DOI: 10.1007/bf00282797
|View full text |Cite
|
Sign up to set email alerts
|

A novel transposon-like structure carries the genes for pyocin AP41, a Pseudomonas aeruginosa bacteriocin with a DNase domain homology to E2 group colicins

Abstract: The genetic determinant for pyocin AP41, a bacteriocin produced by Pseudomonas aeruginosa, has been cloned. The determinant is located on the chromosome flanked by a pair of inverted repeats, forming a transposon-like structure (TnAP41). TnAP41 possesses some features characteristic of the Tn3 family of transposons. Based on a comparison with the structure of the corresponding region of the chromosome of a non-producer strain, we propose that P. aeruginosa has acquired pyocinogeny by the transposition of TnAP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…They are distinguished by their different receptor specificities. Recently we have cloned and sequenced the genetic determinants for pyocins AP41, S1, and S2 (18,20). Each determinant for these three pyocins constitutes an operon encoding two proteins of different sizes, one responsible for killing (the killing protein) and the other conferring immunity to its own pyocin (the immunity protein).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are distinguished by their different receptor specificities. Recently we have cloned and sequenced the genetic determinants for pyocins AP41, S1, and S2 (18,20). Each determinant for these three pyocins constitutes an operon encoding two proteins of different sizes, one responsible for killing (the killing protein) and the other conferring immunity to its own pyocin (the immunity protein).…”
mentioning
confidence: 99%
“…The less highly conserved N-terminal halves have been suggested to be receptor-binding domains because these pyocins show different receptor specificities. In addition to causing breakdown of the chromosomal DNA, pyocins Si and S2, but not pyocin AP41, inhibit lipid synthesis in the susceptible bacteria, although their susceptible strains are not the same (16,18,20).In the study described here, we constructed various chimeric pyocins and domain-deleted pyocins on the basis of their sequence conservation and attempted to determine the functions of each domain by examining their functions in vivo and in vitro.JM109 (26), and MV1304 (25) were used as host strains. For preparation of pyocins and chimeric proteins, E. coli C600 carrying the appropriate plasmids was employed.…”
mentioning
confidence: 99%
“…The trypsin fragment just caused a nick on a DNA molecule with an equivalent molar ratio of a protein and a substrate DNA, even under our optimal in vitro conditions (Fig. 2B, lane h) composition of the fragment and the deduced amino acid sequence, the trypsin fragment is considered to comprise 120 or 121 amino acids, including the carboxyl-terminal part of the large component (13). Figure 3 shows the sequences of the trypsin fragment and T2A, a similar protein of colicin E2, in which processing with trypsin does not increase DNase activity (1,4,8,16).…”
mentioning
confidence: 83%
“…However, the DNase activity observed in vitro alone is not sufficiently potent to explain the single-hit killing in vivo, since DNA molecules are not considerably degraded in vitro compared with in vivo with equivalent amounts of colicin molecules (16). Our recent findings showed that the large subunits of pyocin AP41 and E2 group colicins share the homologous domain of DNase (13), suggesting that pyocin AP41 possesses DNase activity. Pyocin AP41 also might be multifunctional in its mode of killing, since the large subunit of pyocin AP41 is a rather large molecule having an extra domain compared with E2 group colicins and homologous S-type pyocins Si and S2 (14).…”
mentioning
confidence: 88%
See 1 more Smart Citation